Condition of Coral Reefs and Abundance of Coral Fishes of the Chaetodontidae Family in the Waters of Sironjong Gadang Island, Pesisir Selatan District, West Sumatra Province - Satyawira, Immanuel Grahan Deyon; Thamrin, Thamrin; Mubarak, Mubarak (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
Sironjong Gadang Island is one of the islands in the Mandeh Tourism area in Pesisir Selatan Regency, West Sumatra, Indonesia. One of the ecosystems affected by tourism activities is coral reefs. Monitoring the coral reefs' condition and the abundance of coral fish in the Chaetdontidae family is carried out to find out this. This research uses survey research methods. The temperature measurement results obtained an average of 30.2oC, current speed measurements received an average of 0.12 m/s, salinity measurements obtained an average of 30 ppt, and brightness measurements show that the brightness of these waters is 9 m. Tide measurements in the waters of Sironjong Gadang Island, carried out on March 7–8, 2023, are double daily tides (semi diurnal tide). Then, the results from the coral reef cover of Sironjong Gadang Island waters obtained a percentage ranging from 2.34 - 12.83%, with an average rate of live coral reef cover of 5.96%, which is included in the poor category. Furthermore, the results at each research station in the waters of Sironjong Gadang Island showed that 54 coralfish individuals were found, with the number of coralfish at each depth ranging from 4 - 10 individuals. The most common types of coral fish are species. Acuminate had 18 individuals; the fewest types of coral fish found were Chaetodon trifasciatus and C. tristichous, each numbering two individuals. There is a solid relationship between live coral reef cover and the abundance of coral fish in the Chaetodontidae family, where live coral reef cover influences the plenty of coral fish by 61.11%, which means that the higher the percentage of live coral cover, the higher the value of coral fish abundance